JSE 29:3 Fall 2015 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2015)
In 2010, I wrote a pair of editorials dealing with issues concerning peer review and the quality of papers appearing in the JSE. While I’m not so naïve as to think that my editorials exert any great influence (or even that JSE subscribers actually read them), I’m nevertheless a bit surprised to find—five years later—that I still receive a fairly steady stream of complaints about our peer review process. Those complaints fall primarily into two broad categories: (1) charges of rigidity, bias, or tyrannical censorship from authors whose papers were rejected, and (2) complaints from readers who believe that papers appearing in the JSE should never have survived peer review. So I’m thinking it’s time to review the issues again. And since I don’t believe I can substantially improve on what I wrote five years ago, I offer below, in a spirit of unjustified optimism, my two earlier editorials for your (re)consideration.